EXPLORING ETHNOMATHEMATICS IN THE PROCESS OF MAKING TOFU IN DESA PENAMPAAN, ACEH TENGGARA REGENCY, AS A SOURCE OF MATHEMATICS LEARNING - Lisra Mahfirah; Reflina (Pena Cendekia Insani, 2025)
This study explores the mathematical concepts involved in tofu-making through an ethnomathematics approach, linking cultural practices with mathematics education. Using qualitative methods, including interviews, observations, and documentation, the research identifies seven stages in tofu production where mathematical concepts such as arithmetic, geometry, time comparison, and ratios are applied. Findings suggest that these concepts, which are relevant to school mathematics, can serve as a contextual learning resource. The study emphasizes the importance of integrating local culture into mathematics teaching, demonstrating that everyday activities like tofu-making offer valuable real-world applications for learning mathematical principles. This approach enhances students' understanding by connecting theory with practical, cultural contexts.